Penang-Songkhla Land-Bridge Project - A beginning of a new era: Some issues in consideration - Al Haq, M Ashraf (Universiti Utara Malaysia, 1995)
The proposal to setup an integrated rail-ma&pipeline (RRP) system, called the Land Bridge Project (LBP) would link up the sea-pats of Butterworth and Songkhla. The entire project is under the private sector initiative. The consortium is building the project on the assumption of maximising the present infrastructure. The consoritum is hopeful to reduce the traffic congestion and indirectly the level of pollution in the Straits of Malacca. But many agencies have posed questions such as Malaysian Institute of Maritime Affairs (MIMA). Government needs to ensure that the study is not necessarily left to the private sector alone, rather it should join and verify during the study is in progress and even invite international experts to ensure that all the necessary precautionary measures were taken and hence approved the project to be implemented. The theme of the paper is to caution the parties concerned not to refrain from the primary objective. The LBP was initiated to safeguard the environment, therefore the social cost and benefit needs to be considered first in the CBA analysis. Profit and cost from business point of view should not override the social one. Another important concern is, if the sea is busy, most likely the land route remains unaffected. But if the freight (or traffic) is diverted from sea to road, the congestion might multiply to the road as well, whereas the traffic in the Straits remains almost unchanged, because, according to the MIMA estimates, only 10 to 15 per cent of the traffic of vessels can be lessened from the Straits, and which, according to their experts estimates, it will not benefit much to the Straits traffic congestion. Therefore, if one vessel is unloaded, several lorries are required to transship the containers and which might aggravate the already worsened situation.This paper attempts to raise such few queries and therefore request the authorities concerned to look into these issues before giving the signal to go ahead, so as to minimize the errors as much as possible and ensure long run environment friendly solution.